2020
DOI: 10.1158/2159-8290.cd-19-0644
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals Stromal Evolution into LRRC15+ Myofibroblasts as a Determinant of Patient Response to Cancer Immunotherapy

Abstract: With only a fraction of patients responding to cancer immunotherapy, a better understanding of the entire tumor microenvironment is needed. Using single-cell transcriptomics, we chart the fi broblastic landscape during pancreatic ductal adenocarcinoma (PDAC) progression in animal models. We identify a population of carcinoma-associated fi broblasts (CAF) that are programmed by TGFβ and express the leucine-rich repeat containing 15 (LRRC15) protein. These LRRC15 + CAFs surround tumor islets and are absent from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
709
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(766 citation statements)
references
References 72 publications
(73 reference statements)
56
709
1
Order By: Relevance
“…Correlation network analysis of genes differentially expressed in pseudotime, along each trajectory, was then used to identify pseudotime gene expression modules ( Fig. 2e-f and Supplementary Tables 4&5). Similar to scRNA-seq analysis of human head and neck squamous cell carcinoma 10 and pancreatic adenocarcinoma 11,12 we identified a myofibroblastic-CAF subpopulation (CAF4) with upregulated expression of previously described CAF markers (e.g. ACTA2, POSTN and FAP).…”
Section: Diffusion Mapsupporting
confidence: 69%
See 2 more Smart Citations
“…Correlation network analysis of genes differentially expressed in pseudotime, along each trajectory, was then used to identify pseudotime gene expression modules ( Fig. 2e-f and Supplementary Tables 4&5). Similar to scRNA-seq analysis of human head and neck squamous cell carcinoma 10 and pancreatic adenocarcinoma 11,12 we identified a myofibroblastic-CAF subpopulation (CAF4) with upregulated expression of previously described CAF markers (e.g. ACTA2, POSTN and FAP).…”
Section: Diffusion Mapsupporting
confidence: 69%
“…This is likely due to incomplete understanding of fibroblast heterogeneity and their precise role in tumour progression, which is exemplified by reports of both tumour-promoting and suppressive effects 7 . The diverse roles attributed to fibroblasts may be regulated by distinct subpopulations, such as those previously described in the dermis 8 , fibrotic lesions 9 and in multiple solid cancers [10][11][12] . Cancer associated fibroblast (CAF) subpopulations are known to include myofibroblastic and inflammatory phenotypes 3, 11 . However, the extent of phenotypic diversity and the underlying molecular mechanisms regulating this heterogeneity remain unclear.…”
Section: Main Textmentioning
confidence: 94%
See 1 more Smart Citation
“…Cancer associated fibroblasts mainly function to remodel the extracellular matrix in the tumor microenivironment 57 . Recently, a scRNA-seq study of CAF in pancreatic cancer revealed a LRRC15 + CAF population that correlated with poor response in patients treated with anti-PD-L1 therapy 58 . A few of the fibroblasts in our study also express LRRC15 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has proved that tumor microenvironment plays an essential role in the process of pancreatic cancer (38)(39)(40)(41). Immune cells and stromal cells, the two main types of nonneoplastic components, have been reported to accelerate tumor immune escape and progression (42,43).…”
Section: Discussionmentioning
confidence: 99%